Forging Resilient Characters: SD Plus Darul Ulum's Holistic Approach to Education in a Globalized World - Zulfikar, Afifa (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2024)
This research explores the character-building programs at SD Plus Darul Ulum, Jombang, focusing on how they cultivate resilience and toughness in students. The study delves into distinctive programs, including the Pioneering International Primary School, "Everyday with Al-Qur’an," Full Day School, and Outdoor Learning initiatives. Theoretical frameworks encompass globalization of education, holistic learning, extended learning time, and experiential learning. Qualitative methods involve interviews, focus group discussions, observations, and document analysis. Findings reveal the alignment of programs with global standards, holistic Islamic education, extended learning principles, and a comprehensive approach to student development. The research contributes to character education literature, addresses a gap in primary school research, and offers insights for educators and policymakers. It emphasizes the holistic nature of education, transcending traditional paradigms, and positions SD Plus Darul Ulum as a beacon for character development in the 21st century.